2014
DOI: 10.4103/1119-3077.127549
|View full text |Cite
|
Sign up to set email alerts
|

Perception of child adoption among parents/care-givers of children attending pediatric outpatients′ clinics in Enugu, South East, Nigeria

Abstract: Continued advocacy and public enlightenment campaigns should be strengthened in order to harmonize adoption process in our setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 1 publication
2
29
0
Order By: Relevance
“…In Nigeria, separate studies from Kano, Ibadan and Enugu indicate that foster parenting is more prevalent than child adoption 25,26,27 . A study in Enugu, south eastern Nigeria revealed that majority of the respondents prefer to adopt a child in the neonatal age group with slight preference for the male gender 28 .…”
Section: Peculiarities and Challenges Of Child Adoption In Nigeriamentioning
confidence: 99%
“…In Nigeria, separate studies from Kano, Ibadan and Enugu indicate that foster parenting is more prevalent than child adoption 25,26,27 . A study in Enugu, south eastern Nigeria revealed that majority of the respondents prefer to adopt a child in the neonatal age group with slight preference for the male gender 28 .…”
Section: Peculiarities and Challenges Of Child Adoption In Nigeriamentioning
confidence: 99%
“…This makes every family to desire a child. Despite these genuine reasons for adoption, it has been discovered that some buy children for rituals while some trade them for money, depriving them their right to life [2].…”
Section: Introductionmentioning
confidence: 99%
“…According to [10], human trafficking is a major human rights violation, which United Nations in 2000 set up the Palermo protocols, tagged "Protocol to prevent, suppress, and punish trafficking in persons, especially women and children" (Palermo Protocol, 2013) [11]. The section 3(a) of this document defines child trafficking as the recruitment, transportation, transfer, harboring or receipt of persons by means of threat or the use of force or other means of coercion, abduction, fraud, deception, abuse of power or a position of vulnerability or the giving or receiving of payments or benefits to achieve the consent of a person having control over another person, for the purpose of exploitation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations